IBM Pemberdayaan Masyarakat dalam Penanganan Demam pada Anak dengan Water Tepid Sponge - Fitri Wahyuni; Yuni Astuti; Mei Suraning Tias; Wahyuni Agustina; Titah Pramesti (Natural: Jurnal Pelaksanaan Pengabdian Bergerak bersama Masyarakat., 2024)
Children under 5 years of age have an immune system that is still developing, not perfect and not yet strong. This is what causes children to be susceptible to disease. The diseases most frequently experienced by toddlers in Indonesia are flu, diarrhea, rotavirus, allergies, asthma, hand, foot and mouth disease and Fever. Fever is condition when the body temperature rises or is above normal. Efforts to treat fever by providing pharmacological and non-pharmacological therapy. Pharmacological therapy can be carried out by administering antipyretics, while non-pharmacological therapy includes Water Tepid Sponge. Increase knowledge is urgently needed to strengthen awareness in increasing knowledge and behavior in handling fever. One of the efforts made is health education activities about treating fever with Water Tepid Sponge. The result of this community service activity is that there is an increase in knowledge and skills regarding treating fever with Water Tepid Sponge before and after providing Health Education.